ANALYSIS OF RELATIONSHIP INCOME OF RICE FARMERS (Oryza Sativa) IN AGRICULTURAL AND NON-AGRICULTURAL SECTORS IN VARIOUS LAND AREA IN SUB-DISTRICT AIKMEL KABUPATEN LOMBOK TIMUR: ANALYSIS OF RELATIONSHIP INCOME OF RICE FARMERS (Oryza Sativa) IN AGRICULTURAL AND NON-AGRICULTURAL SECTORS IN VARIOUS LAND AREA IN SUB-DISTRICT AIKMEL KABUPATEN LOMBOK TIMUR - Edy Hermawan; Muhammad Anwar (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
Rice commodity in Aikmel sub-district is one of the main commodities with an area of ​​9,392 Ha of lowland rice farming and geographically. Non-agricultural activities in rural areas began to develop in response to insufficient income from the agricultural sector. Many rural residents engage in non-agricultural activities when the agricultural sector is free. This is what causes a large number of residents to work from the non-agricultural sector, related to employment and income opportunities. Seeing this condition, it is felt that research needs to be done. This study aims to look at the income of paddy rice farming, non-farming and the relationship between lowland rice farming income and non-farming income on various land areas. The method in this study, namely descriptive, data collection by survey technique, determining the number of samples were 30 people was carried out by quota sampling and taking farmers in each village was carried out by proportional random sampling and determination of villages as samples was carried out by purposive sampling. The Results of the study explain: 1) the average total income of lowland rice farming farmers is Rp. 1.207.412/LLG or equivalent to Rp. 5.219.359/Ha. 2) In this study, farmers receive an average non-farming income of rice farmers of Rp. 8,000,000.- planting season 3). Relationship analysis relationship obtained correlation coefficient value of 0,3786 Because it has a positive result with a correlation coefficient value of 0,3786, the larger the land area, the greater the contribution of agricultural sector income to total non-agricultural income.